Odpowiedzi

2009-12-09T08:12:27+01:00
Y = 3x² + bx + c

dla x₁= - 2, y = 0
3*(-2)² + b*(-2) + c = 0
12 - 2b + c = 0
- 2b + c = - 12 |:(-1)
2b - c = 12

dla x₁= 1, y = 0
3 * 1² + b * 1 + c = 0
3 + b + c = 0
b + c = - 3

Tworzymy układ równań
2b - c = 12
b + c = - 3

3b = 9 |:3
b = 3

b = 3
3 + c = - 3

b = 3
c = - 3 - 3

b = 3
c = -6

y = 3x² + 3x - 6
y = - 6

3x² + 3x - 6 = - 6
3x² + 3x - 6 + 6 = 0
3x² + 3x = 0 |:3
x² + x = 0
x(x + 1) = 0
x = 0
lub
x + 1 = 0
x = -1
1 5 1
2009-12-09T09:09:51+01:00
A nie prościej funcję zapisać jako y=3(x+2)(x-1) i to jest y=3Xkwadr+3x-6
x=-6 i po podstawieniu y=84
1 5 1